South African children's influence tactics: what works and when?. Issue 4 (19th November 2018) - Ellis, Debbie; Maikoo, Mishaal
Abstract : Purpose: Family consumption studies have been criticised for using an individualistic or dyadic approach to explore the types of influence strategies that children use to sway parental decisions. In this study, attention is refocused on the voices of South African families within twenty-first-century familial interactions. The purpose of this paper is to explore the prevalence of pester power in South Africa, and to understand the influence strategies used by children and the different categories of products that children attempt to influence the purchasing of. Parental responses to these strategies are also explored to determine their effectiveness. Design/methodology/approach: An exploratory research design using quantitative, but mainly, qualitative data, was used to draw insights from 135 families to understand intra-familial negotiation tactics within the context of family consumption and everyday family life. Thematic content analysis was used to extract themes from the responses. Findings: The findings suggest that children use everyday family interactions as a resource to select successful pester and negotiation tactics. These children have a relatively deep understanding of how to influence their parents by using different tactics, such as emotional appeals, product requests, purchase justifications and bad behaviour. Children were found to have an awareness regarding the circumstances during which these tactics are more effective. Originality/value: The contribution offered by this paper is first to build on calls for perspectives in the African context, when marketing to children and second, to add deeper understanding of the categories that children from South Africa influence, and the negotiating tactics that they use. This also contributes to an understanding of the intra-familial interaction processes leading to the eventual emergence of influence strategies and concomitant consumption behaviour.